RETRACTED: Identification of Microbial Communities in Fermented Food using DNA Barcoding Technique and Development of Novel Method for DNA Isolation from Food Products - Raja, Karukuvel Raja; Selvaraj, Sanjay Prasad; Shanmugam, Rekha; Revuru, Bharadwaj; Ramalingam, Sathishkumar (Asian Journal of Biological and Life Sciences, 2020)
The traditional use of fermented foods is based on native knowledge and the use of locally available plant or animal sources as substrates. Several microorganisms participate in fermentation which includes bacteria and fungus. The present research focuses on identifying the micro-organisms present in batter samples using DNA Barcoding technique and determining novel method for isolation of DNA. Serial dilution in nutrient agar was performed for the isolation of bacteria and yeast. Bacterial and yeast colonies were collected from Sample-1 and Sample-2 and characterized using staining techniques. Using PCR technique, the 16S rRNA and ITS genes from isolated bacterial and yeast colonies have been amplified. The amplified products were further sequenced and the sequences obtained were matched using software for Codon and Code. The organisms were found to be Streptococcus lutetiensis and Saccharomyces cf. Paradoxus. Barcodes were generated and total acidity, volatile acidity and ethanol concentration of batter sample was observed to increase for consecutive rising hours. The ethanol concentration was found to be 10.8±0.2% and 9.6±0.12% for sample 1 and 2. This was found to be significantly higher. A novel approach for DNA extraction was determined and the DNA was isolated and validated using Agarose Gel Electrophoresis. Thus, organisms present in batter food products were identified using DNA Barcoding technique. An easy and reliable method for DNA extraction was also determined.
Keywords: 16S rRNA; DNA Barcoding; Fermented foods; ITS genes; Polymerase Chain Reaction